Gastrointestinal survival and adaptation of antibiotic-resistant enterococci subjected to an in vitro digestion model. (April 2020) - Citterio, Barbara; Mangiaterra, Gianmarco; Meli, Maria Assunta; Cedraro, Nicholas; Roselli, Carla; Vignaroli, Carla; Rocchi, Marco; Biavasco, Francesca
Abstract: The ability of four enterococcal strains to survive human digestion and maintain their antibiotic resistance (AR) traits was investigated to determine the health risk posed by seafood-borne streptomycin-, erythromycin-, tetracycline- and gentamycin-resistant enterococci. After demonstrating ant(6)-I, ermB, tetO and aac(6′)-aph(2″) gene transferability by mating assays, strains were inoculated into a mussel homogenate which underwent in vitro digestion. Digestion reduced plate counts by 2–3 log; qPCR counts decreased by 1.5 log ( E. faecium 22571/2), 2.5 log ( E. faecalis 113324) or did not decrease ( E. faecium 125745 and 6767/2). The much lower plate than qPCR counts seen in E. faecium suggested a viable-but-non-culturable (VBNC) subpopulation. Replica plating on antibiotic-supplemented agar and qPCR demonstrated that maintenance of AR traits was antibiotic-dependent, with a variable amount of erythromycin-, tetracycline- and gentamycin-resistant colonies and no streptomycin-resistant colonies. The seeking of unexpressed/lost AR genes in cells turned antibiotic-susceptible after digestion, identified aac(6′)-aph(2″) in all colonies of E. faecalis 113324 and E. faecium 6767/2, in the 40% of 125745 and in none of the E. faecium 22571/2. In conclusion, after digestion the AR traits of antibiotic-resistant (also VBNC) enterococci contained in seafood may be maintained and transferred to the human microbiota and from it to intestinal pathogens.